High-performance electrocatalysts for oxygen reduction derived from cobalt porphyrin-based conjugated mesoporous polymers - Wu, Zhong-Shuai; Chen, Long; Liu, Junzhi; Parvez, Khaled; Liang, Haiwei; Shu, Jie; Sachdev, Hermann; Graf, Robert; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2014)
A cobalt-nitrogen-doped porous carbon that exhibits a ribbon-shape morphology, high surface area, mesoporous structure, and high nitrogen and cobalt content is fabricated for high-performance self-supported oxygen reduction electrocatalytsts through template-free pyrolysis of cobalt porphyrin-based conjugated mesoporous polymer frameworks. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrocatalyst; metalloporphyrin; oxygen reduction; polymer frameworks; pyrolysis